Towards Learner-Oriented Teacher and Educational Support Professional Education Through Personalized Learning - Alisauskiene, Stefanija (Special Education, 2022)
The article shares with the main outcomes that were achieved while developing, implementing and testing innovative practices of personalized learning within the teacher education systems through strategic partnership of teacher education centres in Lithuania, e.g. Siauliai Academy of Vilnius University, Vilnius University, and Vytautas Magnus University, in cooperation of University of Iceland and University College Cork, Ireland. In this paper, the author shares with the main issues of the achievement related to: developed innovative teacher education approach through adopting personalized learning-based framework; updated teacher education study programmes based on the PL concept; and manifestation and evidence of the implemented personalized learning-based concept in teacher education. The methodology of this study is based on a secondary data analysis, including analysis of the INTERPEARL[1] achievement reports. The knowledge and experiences gained within INTEREARL project prove the supposition that in a student-centred paradigm, the role of the teacher changes but becomes otherwise important. The teacher acts as a facilitator, employing flexible pacing and differentiated assessment practices rather than transferring the knowledge to students. Together with other relevant issues, two aspects are most important in a student-centred learning process: the ability to choose activities and assessment methods, and the willingness to take responsibility, which has an impressive impact on the outcomes